The Effect of Physiological Status and Pregnancy on Histological Structure and Hormonal Levels of Ovary and Uterus in Mice Mus Musculus - Hassan, Shaimaa Hameed (Universitas Muhammadiyah Sidoarjo, 2025)
The reproductive system in female mammals is highly dynamic, with significant structural and hormonal changes occurring during the estrous cycle and pregnancy to support fertilization, implantation, and fetal development. In mice (Mus musculus), understanding the histological and hormonal variations in the ovary and uterus is crucial for advancing reproductive biology, disease control, and experimental models in biomedical research. Despite extensive studies on reproductive physiology, few have integrated hormonal profiling with detailed histomorphological changes across different reproductive phases in mice. This study aimed to investigate the effects of physiological status and pregnancy on ovarian follicle development, uterine histology, and hormonal regulation in adult female mice. Sixty ovaries and uteri were examined across six reproductive stages, revealing significant changes in follicular growth, corpora lutea formation, and endometrial structure. Estrogen peaked during estrus, stimulating Graafian follicle development and a thin endometrium, while progesterone dominated pregnancy, maintaining uterine quiescence and promoting decidualization. Pregnancy induced marked endometrial vascularization, increased myometrial thickness, and glandular proliferation, supporting implantation and fetal nourishment. This study is among the first to comprehensively correlate histological remodeling with hormonal dynamics across reproductive stages in mice. The findings enhance understanding of the endocrine–morphological interplay underlying reproductive success and provide valuable baseline data for future research in reproductive biology, fertility regulation, and comparative anatomy. Highlights: Significant hormonal fluctuations were observed across reproductive stages, with estrogen peaking during estrus and progesterone dominating pregnancy. Pregnancy induced major uterine changes, including increased vascularization, decidualization, and myometrial hypertrophy to support implantation and fetal development. Ovarian histology revealed dynamic follicular development, luteal formation, and atresia patterns influenced by hormonal regulation.